Foreign Tourists’ Revisit Intention Approach Applied in the Indian Tourism Market - Bandaru, Ramakrishna; Venkateshwarlu, H. (Indian Journal of Marketing, 2020)
The tourism market is one of the largest sources of foreign exchange earnings for many countries in the world, including India. The travel & tourism market contributed around 10.4% to world GDP and 10% to total employment. The tourism sector contributed about 9% to total GDP in India in 2018. Tourists are the consumers in the tourism market and broadly, they are divided into domestic and foreign tourists. In the tourism market, foreign tourists’ attraction is more important than the domestic tourists. The flow of foreign tourists into the country can help to earn valuable foreign exchange earnings. Therefore, the present study aimed to identify the factors which influence the foreign tourists’ revisit intention with specific reference to heritage tourist destinations. The study focused on the examination of the relationship between tourism attributes (tourism accessibility, accommodation, attraction, core heritage tourism experience) and foreign tourists’ revisit intention. A total of 289 responses were collected using a close-ended questionnaire. The data were examined with the help of confirmatory factor analysis and structural equation modelling using AMOS software. The results unveiled that all the identified tourism attributes had a constructive relation with foreign tourists’ satisfaction and revisit intention. Besides the results, theoretical and practical implications, limitations, and suggestions were also discussed.